Integrating Islamic Values in English Learning through Islamic Stories: Students’ Perspective - Rahmatika, Lutfi Aprilia; Izzah, Lidiyatul Izzah (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2024)
This research was aimed to examine students’ perspective in the integration of Islamic values into English learning through Islamic short-stories. This was an inferential quantitative method by using percentages in reporting the data. The participants were 31 grade X students from Islamic High School Al-Ghozali, Gunung Sindur, West java, Indonesia. In collecting the data, a 5-Likert Scale questionnaire ranging from ‘strongly agree’ (5) to ‘strongly disagree’ (1) used as the instrument. This questionnaire was firslty validated through face-validity. There were 14 items consisted of 10 positive statements and 4 negative ones modified in this questionnaire. The data were analyzed quantitatively and then reported in narratives. The results of data analysis revealed that majority of the students gave positive perspective to the integration of Islamic values into English class through Islamic stories. Most of them agreed that the learning was fun, enjoyable, helped them to understand English better, enriched their vocabularies and made them able to differentiate between Western and Islamic cultures and apply all good lessons in their daily live.